2019
DOI: 10.1017/sjp.2019.33
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postnatal Depression among Primipara Mothers

Abstract: In recent years postnatal depression (PND) has become one of the most important public health issues because of its prevalence. Estimates for those affected by PND suggest a range of 10–15% of new mothers worldwide. In the context of Saudi society, attitudes toward this disorder are influenced by various beliefs, traditions, cultural factors, and values. These variables trigger considerable disparity in terms of frequency of symptoms. The symptoms of postnatal depression vary and can arise over a period of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Although previous personal and family resources have been related to emotional health in other areas of family care [ 38 , 39 ], their study in puerperium has been scarce and inconclusive with only a few studies that analyse issues related to personal and family resources [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Therefore, further research is needed on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous personal and family resources have been related to emotional health in other areas of family care [ 38 , 39 ], their study in puerperium has been scarce and inconclusive with only a few studies that analyse issues related to personal and family resources [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Therefore, further research is needed on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of a similar study showed that the women who had their husband's support for the child care and women who had contented marital relationship had lower risk of having postnatal depression [16]. Another study confirmed the significant association of social support with postnatal depression and suggested that the lack of home support was a contributory factor towards having postnatal depression among puerperal women [17].Gebregziabher et al found the lack of support from husband as a significant risk factor for developing postpartum depression [18]. The logistic regression analysis done by Ozmen et al measured a significant association of perceived social support from significant other and perceived social support from family with postnatal depression, however, no association was found between perceived social support from friends with postnatal depression [19].…”
Section: Discussionmentioning
confidence: 96%
“…The development of this pathology during the postpartum period seems to be related to the hormonal alterations that occur during this period 4 . Other factors that increase the probability of its development have been identified, including (i) a history of psychiatric disorders (history of depression, anxiety or depression in pregnancy or postpartum depression) 7 , 10 ; (ii) stressful life events (including stressors related to childcare), problems in the marital relationship, and lack of support 11 , 12 ; (iii) sociodemographic characteristics (low educational or socioeconomic level, absence of a partner, or unemployment) 7 , 13 ; and (iv) some clinical circumstances, such as caesarean delivery, primiparity, and complications during pregnancy 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%